2022
DOI: 10.3389/fimmu.2022.993187
|View full text |Cite
|
Sign up to set email alerts
|

A robust CD8+ T cell-related classifier for predicting the prognosis and efficacy of immunotherapy in stage III lung adenocarcinoma

Abstract: Patients with stage III lung adenocarcinoma (LUAD) have significant survival heterogeneity, meanwhile, CD8+ T cell has a remarkable function in immunotherapy. Therefore, developing novel biomarkers based on CD8+ T cell can help evaluate the prognosis and guide the strategy of immunotherapy for patients with stage III LUAD. Thus, we abstracted twelve datasets from multiple online databases and grouped the stage III LUAD patients into training and validation sets. We then used WGCNA and CIBERSORT, while univaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Meanwhile, other researchers were dedicated to the information on the tumor microenvironment. Jinteng Feng et al constructed a nomogram associated with CD8 + T cells to predict survival rates and immunotherapy benefits of stage III LUAD patients (30). A moderate performance showed in an online database that their prediction model had approximately 0.649-0.709 AUC, but a survival difference between the two groups (highand low-risk groups) was not observed (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, other researchers were dedicated to the information on the tumor microenvironment. Jinteng Feng et al constructed a nomogram associated with CD8 + T cells to predict survival rates and immunotherapy benefits of stage III LUAD patients (30). A moderate performance showed in an online database that their prediction model had approximately 0.649-0.709 AUC, but a survival difference between the two groups (highand low-risk groups) was not observed (30).…”
Section: Discussionmentioning
confidence: 99%
“…Jinteng Feng et al constructed a nomogram associated with CD8 + T cells to predict survival rates and immunotherapy benefits of stage III LUAD patients (30). A moderate performance showed in an online database that their prediction model had approximately 0.649-0.709 AUC, but a survival difference between the two groups (highand low-risk groups) was not observed (30). A similar study used the next-generation sequencing method mainly; these predictive models might be limited to being widely applied for lack of gene sequencing data, which might be too expensive for most patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these are neoantigens that induce tumor-specific immune responses. 32 34 Activated CD8+ T cells are responsible for tumor cell recognition and lysis, the mechanisms of which have been described in detail, involving the release of cytotoxic particles. Interestingly, in most tumors, invasive cytotoxic T cells express inhibitory receptors (e.g.…”
Section: The Components Of Time and Their Roles In Luad Developmentmentioning
confidence: 99%
“…programed death-1 (PD-1), Tim-3, and Lag-3) whose function in physiological situations is to suppress the immune response when bound to their ligands. 32 34 In fact, many tumor cells can take advantage of this inhibitory mechanism and express multiple ligands (e.g. PD-L1, PD-L2) to help them escape T-cell attacks.…”
Section: The Components Of Time and Their Roles In Luad Developmentmentioning
confidence: 99%
“…A previous report demonstrated the clinical relevance of UPB1 variants as an indicator of fluoropyrimidine-related toxicity in East Asians. Recent studies have shown that UPB1 plays a key role in various cancers, such as LUAD, 14 hepatocellular carcinoma (HCC), 15,16 and clear cell renal cell carcinoma. 13,17 A study revealed that UPB1 may be a protective factor in LUAD and that UPB1 expression is associated with CD8+ T cells.…”
mentioning
confidence: 99%